COMPARATIVE STUDY OF CRIMINAL LAW AND SHARIA LAW (CASE STUDY: MINOR WORKERS) - Aulia, Gavinella; Mandasari Saragih, Yasmirah; Zarzani, T. Riza (Universitas Efarina, 2024)
A child is someone who is still underage, whether male or female. The phenomenon of children as workers often occurs. The reality shows that poor families really need jobs for their children to help the family economy and for their own lives. In this research, the author examines